Simple synthesis of novel magnetic silver polymer nanocomposites with a good separation capacity and intrinsic antibacterial activities with high performance. Issue 43 (15th October 2021) - Soleymani-Babadi, Susan; Beheshti, Azizolla; Nasiri, Elahe; Bahrani-Pour, Maryam; Motamedi, Hossein; Mayer, Peter
Abstract : Two new nanocomposites containing the MnFe2 O4 of the unprecedented Ag complexes with N- and S-donor ligands were synthesized. The nanocomposites can be prepared by a simple procedure and use efficiently for antibacterial activity and other purposes. Abstract : Two new coordination polymers namely, [(AgCN)4 L S ] n (1 ) and [(AgCN)3 L N ] n (2 ), were successfully synthesized by the reaction of AgNO3 and cyanide as a co-anion with L S [1, 1′-(hexane-1, 4-diyl)bis(3-methylimidazoline-2-thione] and L N [1, 1, 3, 3-tetrakis(3, 5-dimethyl-1-pyrazole)propane] ligands in order to use them for the preparation of magnetic nanocomposites with MnFe2 O4 nanoparticles by an efficient and facile method. They were then well characterized via numerous techniques, including elemental analysis, FT-IR spectroscopy, TGA, PXRD, SEM, TEM, EDX, VSM, BET, ICP, and single-crystal X-ray diffraction. The considered polymers and their magnetic nanocomposites with nearly the same antibacterial activity demonstrated a highly inhibitive effect on the growth of Gram-negative ( Escherichia coli, Pseudomonas aeruginosa ) and Gram-positive ( Staphylococcus aureus, Bacillus subtilis ) bacteria. By considering the simple separation and recyclable characters of the magnetic nanocomposites, these materials are suitable to be used in biological applications.